Prevalence of dyslipidemia in South Indian adults: an urban-rural comparison - S., Ajay Raj; K, Sivakumar; K, Sujatha (International Journal Of Community Medicine And Public Health, 2017)
Background: Coronary artery disease (CAD) is a major cause of morbidity and mortality in industrialized countries, and is one of the major public health problems globally. There is an emerging evidence of premature CAD occurring in Asian Indians, at least 10 years earlier as compared to other ethnic groups. Dyslipidemia is a consequence of modernization because the prevalence of dyslipidemia is higher in urban than rural areas. In this context, the present study was aimed to determine lipid levels and to compare the lipid levels and prevalence of dyslipidemia in a rural and urban community in Tamil Nadu. Methods: This is a descriptive cross-sectional study done on Adults ≥ 30 years of age residing in the Field practice area of Rural Health Centre and Urban Health Centre, Division of Community medicine, Rajah Muthiah Medical College, Annamalai University. This study included Interview schedule, Anthropometry, Blood pressure measurement and Fasting lipid profile on 325 subjects of whom 165 and 160 belong to urban and rural population respectively. Results: The study revealed higher prevalence of dyslipidemia, which was marginally higher in the urban (74.5%) than the rural (68.8%) area but the difference was statistically not significant (p value=0.246). The extents of high total cholesterol, LDL cholesterol, triglycerides were marginally higher in the urban area but the difference was statistically not significant. There is a linear association between the prevalence of dyslipidemia, age and body mass index. Conclusions: Our study concluded the higher percentage of dyslipidemia both in the urban and rural population. Hence, awareness programmes on desirable diet and regular screening of population on periodic basis should be incorporated at the primary health care level.